Investigating the Effects of English-Medium Instruction on Students’ Vocabulary Use . A Case Study of the Computer Science Department at Souk Ahras University - Majda SAADAOUI (My University, 2025)
Abstract This study aims to investigate the impact of English Medium Instruction (EMI) on the vocabulary use of computer science students in academic contexts. It aims also to identify the challenges students face in vocabulary learning within EMI settings. The research addresses two main questions: the challenges students face in vocabulary learning and use within EMI settings, and the extent to which students use computer science vocabulary accurately and appropriately in academic contexts. We adopted a quantitative experimental design method in this study, the sample consisted of 40 undergraduate computer science students. Data were collected through a students’ vocabulary questionnaire in order to address the challenges that students face in vocabulary learning within EMI settings, pre and post vocabulary tests to assess the accuracy and appropriateness of students’ use of computer science-related vocabulary in academic contexts, and a paired t-test analysis to measure changes in vocabulary performance. The findings of the study show that while most students adapt well to EMI, a significant number of them encounters difficulties with technical vocabulary, pronunciation, and comprehension, which affect their lecture understanding and active vocabulary use. The results also show a statistically significant improvement in students’ vocabulary scores after EMI exposure, indicating positive effects on both general and specialized vocabulary acquisition. We recommend for enhancing vocabulary instruction, providing specialized training for teachers, and creating supportive learning environments to maximize the benefits of EMI. This research provides an empirical evidence of EMI impact on vocabulary use in the field of computer science, offering insights for educators, curriculum designers, and policymakers aiming to improve EMI programs. ------------ الملخص تهدف هذه الدراسة إلى التحقيق في تأثير التعليم باللغة الإنجليزية كلغة وسيطة على استخدام الطلاب للمفردات المتعلقة بعلوم الحاسوب في السياقات الأكاديمية، كما تهدف إلى تحديد التحديات التي يواجهها طلاب علوم الحاسوب في تعلم المفردات ضمن بيئات التعليم باللغة الإنجليزية. تتناول هذه الدراسة سؤالين رئيسيين والمتمثلان في: التحديات التي يواجهها الطلاب في تعلم واستخدام المفردات في بيئات التعليم باللغة الانجليزية. تم اعتماد المنهج الكمي في هذه الدراسة، حيث جُمعت البيانات من خلال استبيان حول مفردات الطلاب المستخدمة في علوم الحاسوب لتحديد التحديات التي يواجهونها، بالإضافة إلى اجراء اختبارات متعلقة بمفردات قبل وبعد التدخل التعليمي، وتحليل اختبار مزدوج لقياس التغيرات في مدى دقة وملائمة استخدام الطلاب لمفردات علوم الحاسوب في السياقات الأكاديمية. أظهرت النتائج أن معظم الطلاب يتكيفون جيدًا مع التعليم باللغة الإنجليزية، إلا أن عددًا كبيرًا منهم يواجه صعوبات في المفردات التقنية، والنطق، والفهم، مما يؤثر على فهمهم للمحاضرات واستخدامهم النشط للمفردات التقنية. كما أظهرت النتائج تحسنًا ذا دلالة إحصائية في درجات الطلاب بالنسبة لمدى تطبيقهم للمفردات بعد التعرض للتعليم باللغة الإنجليزية كلغة وسيطة، وهذا يشير إلى التأثيرات إيجابية على اكتساب المفردات العامة والخاصة في مجال علوم الحاسوب. نوصي بتعزيز تعليم المفردات، وتوفير تدريب متخصص للأساتذة، وخلق بيئات تعليمية داعمة لتعميم فوائد التعليم باللغة الإنجليزية. تقدم هذه الدراسة أدلة تجريبية على تأثير التعليم باللغة الإنجليزية كلغة وسيطة على الاستخدام الملائم للمفردات في مجال علوم الحاسوب بالنسبة للطلاب، كما تمنح هذه الدراسة رؤى للأساتذة ومصممي المناهج وكذا صناع القرار الراغبين في تحسين برامج التعليم باللغة الإنجليزية. ------------ Résumé Cette étude vise à examiner l’impact de l’enseignement en anglais (English Medium Instruction - EMI) de l’English Medium Instruction (EMI) sur l’utilisation du vocabulaire chez les étudiants en informatique dans des contextes académiques. Elle cherche également à identifier les difficultés que rencontrent les étudiants dans l’apprentissage du vocabulaire en contexte EMI. La recherche s’articule autour de deux questions principales : les difficultés auxquelles les étudiants sont confrontés dans l’apprentissage et l’utilisation du vocabulaire en contexte EMI, et dans quelle mesure ils utilisent avec précision et pertinence le vocabulaire lié à l’informatique dans des contextes académiques. Une méthode quantitative a été adoptée. Les données ont été recueillies à l’aide d’un questionnaire sur le vocabulaire afin d’explorer les difficultés des étudiants, ainsi que des tests de vocabulaire (pré- et post-test) pour évaluer la précision et la pertinence de l’utilisation du vocabulaire lié à l’informatique. Un test t apparié a permis de mesurer les changements dans la performance lexicale. Les résultats montrent que, bien que la majorité des étudiants s’adapte à l’EMI, un nombre important rencontre des difficultés avec le vocabulaire technique, la prononciation et la compréhension, ce qui affecte la compréhension des cours et l’utilisation active du vocabulaire. Une amélioration significative des scores de vocabulaire a été constatée après l’exposition à l’EMI, ce qui montre un impact positif sur l’acquisition du vocabulaire. L’étude recommande de renforcer l’enseignement du vocabulaire et de former les enseignants afin de maximiser les bénéfices de l’EMI. Elle fournit des preuves empiriques de son effet dans le domaine de l’informatique et offre des pistes pour améliorer les programmes EMI
Keywords: academic context; computer science students; English Medium Instruction; vocabulary acquisition; vocabulary use; التعليم باللغة الإنجليزية، استخدام المفردات، طلاب علوم الحاسوب، مفردات متعلقة بعلوم الحاسوب، السياق الأكاديمي، اكتساب المفردات; Enseignement en anglais; utilisation du vocabulaire; étudiants d’informatique; acquisition du vocabulaire; vocabulaire lié à l’informatique; contextes académiques.